Answer:
Initial equation: 5x + 2 = 3x + 12
x = 5
Step-by-step explanation:
Point C is the midpoint between A and B.
This means that:
AC = CB
We have that:
AC = 5x + 2
CB = 3x + 12
Since AC = CB, the initial equation is:
5x + 2 = 3x + 12
Now we can solve
5x + 2 = 3x + 12
5x - 3x = 12 - 2
2x = 10
x = 10/2
x = 5
Step-by-step explanation:
it is negative 20 I'm pre sure
Correct so far. Finish up.
.. (x +3)(x)(x -1) = 1170
.. x^3 +2x^2 -3x -1170 = 0 . . . . . . one sign change ⇒ one positive real solution
This is a cubic equation with one positive real solution. There are several possible approaches to solving this. My favorite is to let a graphing calculator show me the solution.
You can also factor 1170 = 13*10*9, so x=10.
The width of the prism is 10 feet; the length is 13 feet; the height is 9 feet.
Answer:
8 and 10
Step-by-step explanation:
8+10=18
Both are even, and consecutive